Impact of Subthalamic Deep Brain Stimulation on Hyposmia in Patients With Parkinson's Disease Is Influenced by Constipation and Dysbiosis of Microbiota - Li, Chao; Hou, Ying; Wang, Xu; Li, Yue-xuan; Li, Feng; Zhang, Chao; Li, Wei-guo (Frontiers in Neurology, 2021)
Abstract Background: Non-motor symptoms in PD usually arise at very early stage and vary during the whole disease progression. Deep brain stimulation (DBS) is considered as a highly efficient treatment option for PD’s motor function. However, the effect of DBS on NMS, especially hyposmia, has not been fully understood and the deep connection between different NMS such as hyposmia and constipation is still unknown. Objective: The objective of this study was to evaluate the therapeutic effect of DBS on hyposmia in PD patients with or without constipation and find potential factors which might influence the efficacy. Methods: A retrospective analysis of 65 PD patients accepted STN-DBS operation in Qilu Hospital during 2019-2020 were conducted to evaluate the exact therapeutic effect of DBS on hyposmia in PD. Sub-group analyses about the relationship between hyposmia and constipation were carried out. Analysis of flora in nasal mucosa was also conducted to evaluate the abundance and variety in different PD groups. Results: Our study showed that DBS had clearly improved olfactory function in Parkinson patients (P=0.012) and subgroup analysis found that PD patients with constipation have lower olfactory function scores (25.27±3.44 vs 33.90 ± 6.633, p = 0.014) and worse improvement after DBS operation (ΔTDI 12.11±3.2 vs 8.78±2.91, p=0.0072). Analysis of flora indicated the obvious discrepancy on olfactory function scores and degree of improvement might be related to the abundance and dysbiosis of microbiota. Conclusion: In summary, this article presents a study on PD with hyposmia and constipation after DBS operation, explored the relationship between different NMS and offer a potential explanation on why PD patients with constipation usually have worse olfactory function for the less abundance and variety of microbiota.